Strategi Pemasaran Berbasis Teknologi Digital Dalam Pengembangan UMKM Terasi Toboali Kabupaten Bangka Selatan - sumarno, Sumarno (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the most prominent economic actors in the Indonesian economy. They can be said to be the primary source of state income, can create many entrepreneurs or entrepreneurs, and open up many job opportunities, which can be the business sector with the most significant contribution to national development. Micro, Small, and Medium Enterprises (MSMEs) are essential to a country's economy. In the digital era, this research aims to explore digital technology-based marketing strategies for MSMEs in Terasi Toboali, South Bangka Regency. The research method used is field research (Field Research), which can be considered a broad approach in qualitative research or a method for collecting qualitative data. The significance is that researchers go to the field to make observations about a phenomenon in a natural setting. The research results show that using digital technology in Terasi Toboali's marketing strategy can help MSMEs increase operational efficiency and reach a wider market. However, obstacles, such as limited access and skills in using digital technology, still need to be overcome. The marine product processed into shrimp paste is Sungkur Shrimp. This processing is a form of innovation for the Toboali people to improve their family's economy.  Regarding product marketing, shrimp paste business actors do not yet have adequate understanding and capabilities. Business actors are quite satisfied with the product marketing they are currently doing. A company's marketing strategy can increase current and future sales. Specifically when using the 4Ps (product, price, location, and promotion) to determine market share, achieve goals, and determine consumers